2010
DOI: 10.1016/j.neuroscience.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and chronic handling alter endocannabinoid signaling and behavioral reactivity to context in adult rats

Abstract: Social deprivation in early life disrupts emotionality and attentional processes in humans. Rearing rats in isolation reproduces some of these abnormalities, which are attenuated by daily handling. However, the neurochemical mechanisms underlying these responses remain poorly understood. We hypothesized that post-weaning social isolation alters the endocannabinoid system, a neuromodulatory system that controls emotional responding. We characterized behavioral consequences of social isolation and evaluated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 123 publications
(148 reference statements)
3
55
1
Order By: Relevance
“…Furthermore, evidence of decreased neuronal synaptic spiny processes have also been found in the hippocampus of IR rats (Silva-Gomez et al, 2003); as well as, decreased cytoskeletal structures associated with dendrites in the hippocampus (Bianchi et al, 2006). Finally, reduced levels of endocannabinoid signaling (Sciolino et al, 2010), altered markers of benzodiazepine signaling (Petkov and Yanev, 1982;Miachon et al, 1990;Harte et al, 2007), reduced axonal lysosomal accumulations (Bagorda et al, 2006), and reduced electrophysiological activity (Greene et al, 2001;Lu et al, 2003;Roberts and Greene, 2003) in the hippocampus of IR rats all support reduced hippocampal neuronal activity in IR rats. Thus, an abundance of data, in addition to our prior finding of reduced IEG activity in this region after isolation rearing (Vitalo et al, 2009), is consistent with the current study's hypothesis that altered PET FDG uptake in the hippocampus of the IR rats can serve as a translational biomarker of neuronal activity in this region.…”
Section: Changes In Fdg Uptake In Hippocampusmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, evidence of decreased neuronal synaptic spiny processes have also been found in the hippocampus of IR rats (Silva-Gomez et al, 2003); as well as, decreased cytoskeletal structures associated with dendrites in the hippocampus (Bianchi et al, 2006). Finally, reduced levels of endocannabinoid signaling (Sciolino et al, 2010), altered markers of benzodiazepine signaling (Petkov and Yanev, 1982;Miachon et al, 1990;Harte et al, 2007), reduced axonal lysosomal accumulations (Bagorda et al, 2006), and reduced electrophysiological activity (Greene et al, 2001;Lu et al, 2003;Roberts and Greene, 2003) in the hippocampus of IR rats all support reduced hippocampal neuronal activity in IR rats. Thus, an abundance of data, in addition to our prior finding of reduced IEG activity in this region after isolation rearing (Vitalo et al, 2009), is consistent with the current study's hypothesis that altered PET FDG uptake in the hippocampus of the IR rats can serve as a translational biomarker of neuronal activity in this region.…”
Section: Changes In Fdg Uptake In Hippocampusmentioning
confidence: 76%
“…These studies have consistently shown that when isolation rearing is imposed during the critical period of development between PN 20 and 30, an abundance of aberrant behavioral and neurobiological abnormalities develop (Comery et al, 1995;Hall et al, 1998;Ago et al, 2002;Preece et al, 2004;Alquicer et al, 2008;Fone and Porkess, 2008;Schubert et al, 2009), particularly the (hippocampus) (Varty et al, 1999;Silva-Gomez et al, 2003;Bianchi et al, 2006;Scaccianoce et al, 2006;Pisu et al, 2011) and the medial prefrontal cortex (mPFC) (Comery et al, 1996;Bagorda et al, 2006;Day-Wilson et al, 2006;Pascual et al, 2006;Sciolino et al, 2010;Quan et al, 2011). The two most prominent behavioral effects in IR compared to group-reared (GR) rats are hyperactivity to novelty (Lapiz et al, 2003;Elliott and Grunberg, 2005) and deficits in prepulse inhibition (Cilia et al, 2005;Day-Wilson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators noted that Sdom rodents and rodents defeated in a resident-intruder test were either more (Blanchard et al 2001;Nikulina et al 2004) or less active than DOM rodents (Blakley and Pohorecky 2006;Meerlo et al 1996). These apparent inconsistencies may be attributed to experimental variables, such as handling and pre-test injection, which may have had significant biobehavioral consequences (Gariépy et al 2002;Hall et al 1997;Sciolino et al 2010). The subjects in our study were extensively handled, injected, and tested in a large non-novel open field arena at both tests, minimizing the anxiety generated by the fear of open spaces, nevertheless their contribution to group differences in these variables remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…It is now clear that eCB system is altered in several neurodegenerative diseases and, very interestingly, that distinct elements of the eCB system in peripheral blood mirror these perturbations, providing novel and noninvasive diagnostic tools for several neuroinflammatory diseases [92,93]. In addition, the eCB system controls emotional responses [94], behavioral reactivity to context [95], and social interaction [96]. Thus, it can be hypothesized that alterations in this endogenous circuitry may contribute to the autistic phenotype.…”
Section: Alterations Of the Ecb System In Autismmentioning
confidence: 99%